UPAYA MEMPERKUAT CITRA RAMAYANA DEPARTEMENT STORE MELALUI PROMOSI PENJUALAN DAN PERIKLANAN - Didit Darmawan; Rahayu Mardikaningsih; Samsul Arifin; Mila Hariani (Universitas Islam Balitar, 2019)
A good corporate image can be formed through marketing communication that is right on target. Marketing communication consists of several elements such as advertising and sales promotions. With attractive sales promotions that are different from competitors and creative and unique advertisements using different themes to attract people's interest and to try what the company offers. This study aims to analyze and discuss the effect of salespromotions andadvertisements on the corporate image of the Ramayana Department Store. The sampling technique uses probability sampling method with a sample random sampling technique. The number of samples involved in this study were 100 respondents. Analysis analysis of collected data is processed through multiple linear regression analysis with SPSS 24.0 software. The results state that salespromotions and advertisements have a significant positive effect on corporate image.